Peran Stakeholder dalam Pembangunan Infrastruktur Jalan dan Jembatan di Desa Sanglar Kecematan Reteh Kabupaten Indragiri Hilir - Tania Saputri; Sujianto Sujianto (Asosiasi Peneliti dan Pengajar Ilmu Hukum Indonesia, 2025)
The development of road and bridge infrastructure has an important role in increasing accessibility, economic growth and community welfare in rural areas. This study aims to analyze the role of stakeholders in the development of road and bridge infrastructure in Sanglar Village, Reteh District, Indragiri Hilir Regency. The research method used is a qualitative approach with data collection techniques through interviews, observation and documentation studies. The research results show that the main stakeholders in infrastructure development include local governments, communities and social institutions. Regional governments play a role in policy formulation, planning and budget allocation. The community participated in the deliberation and development monitoring process. The obstacles faced in development included budget limitations, challenging geographical conditions, as well as inadequate damaged road and bridge infrastructure.This research concludes that synergy between stakeholders is very necessary to increase the effectiveness of road and bridge infrastructure development. More targeted policies and increased community participation are needed at each stage of development so that the results achieved can be sustainable and in line with local needs.